The Impact of Continued Watching English Movie Series on Students’ English Capability (Case Study: Peaky Blinder and Friends) - Karina Putri Djanuwarso; Puput Deskilasari (JEdu: Journal of English Education, 2022)
This study investigates the impact of watching the English-language series of Peaky Blinders and Friends towards the improvement language ability in terms of word pronunciation, long-sentence listening, and grammatical analysis. This point outs the impact of continued exposure to English media to improve the student’s capability of learning English. The study has been arranged for 3 months by involving high school students from SMA 999 in Jakarta with a total sample of 25 students. The data were then gathered through conventional paper-based testing for Listening and grammar proficiency which encapsulated into Reading and Writing section. Speaking assessment was conducted through an interview. The tests were conducted in three main stages, the pre- test, mid-tests and post-test. The mid-tests were held after the first 2 week of the month. The result of the study showed that there were notable improvements in the English skills among 25 students, particularly in the Listening aspects as shown by one-way ANOVA and Tukey HSD analysis. However, the data from other aspects such as Reading, Writing and Speaking despite showed an upward trend, did not produce improvement as significant as Listening aspects. This phenomenon might be caused by the lack of students’ knowledge foundation regarding several language aspects therefore most students require longer time to completely improve their ability. From this point, this study can suggest that using movie series could be a great tool for English education to improve the students’ awareness of English and therefore would naturally improve their English.